PERTANGGUNGJAWABAN PIDANA PELAKU TINDAK PIDANA PENCUCIAN UANG MELALUI TERANSAKSI GAME ONLINE - Putong, Diana Darmayanti; Limbat, Marcellino David; Sanger, Nadia Gloria (Honeste Vivere, 2024)
The perpetrators of money laundering in Indonesia have starting taking advantage of current technological developments. One of them being the transactions of online gaming. This is due to the absence of sanctions that can be imposed. This research aims to explore different money laundering crimes that occur within online gaming in Indonesia and the forms of criminal responsibility for the perpetrators of these crimes. The method used in writing this journal was normative legal research where there is obscurity and emptiness of legal norms in Law Number 8 of 2010 concerning Prevention and Eradication of Money Laundering Crimes (Hereinafter referred to as the TPPU Act). The results of this research showed that the TPPU Law did not yet regulate if there was a phenomenon of money laundering through online gaming, but the perpetrators of money laundering through transactions online game could be charged with Article 47 of Act No. 11 of 2008 concerning Transactions and Electronic Information (hereinafter referred to as Law ITE). The form of criminal liability for money laundering perpetrators through transactions online games can be seen in Article 47 of the ITE Law which states that perpetrators who fulfill the elements of Article 31 paragraph (1) or paragraph (2) are given criminal sanctions in the form of a maximum of 10 years imprisonment and/or fines up to Rp. 800,000,000.00.